Species composition abundance and density of white egrets at three wetland ecosystems in Western Leyte - Lawag, Joyce Faith B. (2017)
Egrets are migratory wading birds that migrate to their wintering grounds in tropical regions to escape from the cold weather in temperate regions. Philippine wetland ecosystems are one of the important wintering sites of these birds. A study on white egret species composition, abundance and diversity was conducted in three wetland ecosystems that primarily aimed to describe and identify the species of white egrets present, to quantitatively assess species abundance and density, and to qualitatively assess species habitat and environmental factors. The study area was visited for four months from January to April 2017. Bird survey time was conducted early in the morning from 0600h- 1000h. The birds were counted by point count and block count method using binoculars and spotting scope. Five species of white egrets were observed and identified in the study area. Identification was then confirmed by a bird expert. Results showed that Egretta garzetta was the most abundant species with a frequency of 319 counts. Kruskal-Wallis test indicates that white egrets population density have significant difference between stations and months (p<0.05). Among the stations, tidal mudflat (station 1) had the highest species population density because of its abundance of food sources, mangrove vegetation and low human disturbances. Also, species population density was at peak during the month of January corresponding to its seasonal migration and less extreme weather conditions. Hence, the study revealed that species abundance and density varies in terms of prey preference, habitat selection, and environmental factors.